2009
DOI: 10.1542/peds.2008-1578k
|View full text |Cite
|
Sign up to set email alerts
|

Recently Trained Pediatric Subspecialists: Perspectives on Training and Scope of Practice

Abstract: OBJECTIVES. Little is known regarding the factors influencing the decision to pursue pediatric subspecialty fellowship training and the timing of when such a decision is made. In addition, there is no information regarding whether the general pediatrics training received in residency is perceived as valuable by subspecialists. This study was conducted to characterize the strengths and weaknesses of residency and fellowship training from the perspective of recently trained pediatric subspecialists and to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 12 publications
1
47
0
Order By: Relevance
“…There is a range of opinions about the numbers of pediatricians needed for the future. 24-26 R 3 P conversations along with resident and practitioner surveys [13][14][15][16] have highlighted progressive segmentation of practice, even among general pediatricians. Competencies are different enough that considerable adaptation, even additional training, will likely be needed to switch from one practice setting to another.…”
Section: Colloquium I: the Future Of Pediatric Health Care Delivery Amentioning
confidence: 99%
See 1 more Smart Citation
“…There is a range of opinions about the numbers of pediatricians needed for the future. 24-26 R 3 P conversations along with resident and practitioner surveys [13][14][15][16] have highlighted progressive segmentation of practice, even among general pediatricians. Competencies are different enough that considerable adaptation, even additional training, will likely be needed to switch from one practice setting to another.…”
Section: Colloquium I: the Future Of Pediatric Health Care Delivery Amentioning
confidence: 99%
“…Surveys of residents, fellows, and practitioners have shown that most programs provide some flexibility in selection of subspecialty electives or access to particular groups of patients, but only one third provide both, and only a few allow residents maximum flexibility to organize their education to match their preferences. [14][15][16] Surveys revealed that most third-year pediatric residents decided on a specific career path early in their third year. This makes it possible to use a portion of the third year, and perhaps of the second, to prepare for a particular career.…”
mentioning
confidence: 99%
“…The Freed et al survey of 7882 pediatrics residents as part of the 2007 American Board of Pediatrics in-training examination 51 sheds light on the pediatrics residency experience. In 3 other articles they examine the perspectives of pediatrics generalists 52 and subspecialists 53 within the first 2 to 5 years after certification, as well as current pediatrics subspecialty fellows 54 regarding their residency experiences and career choices. The tables display the results of additional analyses generated for this commentary: Table 1 compares the answers of generalists and subspecialists to questions about the factors considered in selecting a particular residency program and, generally, how more discretionary, flexible time in residency might be used; Table 2 compares preferences for more learning opportunities in specific content areas; and Table 3 examines the opinions of subspecialists and current fellows regarding the length of time required for residency and fellowship training.…”
mentioning
confidence: 99%
“…For example, Table 1 shows that although geographic location of the residency program was the most important factor for both generalists and specialists, the importance of lifestyle issues, subspecialty expertise/training opportunities, prestige, and patient population varied. Response differences associated with gender, medical school (US or Canadian versus international), size of residency program, and subspecialty are discussed in detail by Freed et al [52][53][54] A second question raised by R 3 P Project participants was: Are current training programs flexible enough to meet training needs both for residents going into general pediatrics and those choosing subspecialty fellowship training? A careful review of the current review committee guidelines for pediatrics reveals a high degree of flexibility, with 8 to 9 months of undifferentiated time across the 33-month (allowing for 3 months of vacation) training period.…”
mentioning
confidence: 99%
See 1 more Smart Citation